A method for preparing SrZnV2O7 microwave dielectric ceramic powder in a short time
Through the new preparation method, low temperature and short-time calcination methods are adopted to solve the problems of high temperature, long time, easy to produce heterogeneous phases and particle agglomeration in the prior art, and high-purity, uniform particles of SrZnV2O7 microwave dielectric ceramics are achieved The preparation of powder improves the sintering quality.
Patent Information
- Application Number
- CN202310703508.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-06-14
AI Technical Summary
In the existing microwave dielectric ceramic powder preparation methods, the preparation temperature is high and the time is long, and it is easy to produce heterogeneous phases and particles agglomerate, resulting in poor sintering quality.
Using a new preparation method, NH4VO3 is dissolved in a water bath in 80°C, and then Sr(NO3)2, Zn(NO3)2·6H2O and glycine are dissolved at room temperature, and then mixed and stirred in a water bath in 70°C to obtain a sol and Dry at 120°C, and finally calcined at 500 to 700°C for 5 minutes to 2 hours to prepare SrZnV2O7 microwave dielectric ceramic powder.
It reduces the preparation temperature and time, reduces production energy consumption, improves particle dispersion and particle size uniformity, and improves sintering quality.
Smart Images

Figure CN116751055B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-metallic material preparation, and specifically relates to a method for preparing SrZnV2O7 microwave dielectric ceramic powder in a short time. Background Art
[0002] Microwave dielectric ceramics refer to new functional ceramic materials that act as dielectric materials and play functions in microwave circuits. They are widely used in dielectric substrates, electronic devices and packaging materials, and are of great value in the fields of communications, electronic products, and aerospace. With the continuous development of information technology, higher requirements are put forward for the miniaturization and integration of microwave devices, so there are more requirements for microwave dielectric ceramics, such as lower dielectric loss, lower sintering temperature, and the ability to meet the characteristics of co-firing with electrodes to improve integration. Low-temperature co-fired ceramic (LTCC) technology and ultra-low-temperature co-fired ceramic (ULTCC) technology can meet the needs of miniaturization and multi-functionality of electronic devices, and are conducive to the realization of high-density assembly of circuits. Since the co-firing technology requires the co-firing of ceramics with internal electrodes, the sintering temperature of LTCC materials must be lower than the melting point of metal electrode Ag (melting point 960°C), and the sintering temperature of ULTCC materials must be lower than the melting point of metal electrode Al (melting point 660°C). SrZnV2O7 is a vanadate microwave dielectric ceramic material. In the document "SrZnV2O7: A low-firing microwave dielectric ceramic with high quality factor", the traditional solid phase method was used to prepare ceramic powder. First, the raw material was ball milled for 9 hours, and then calcined at 625℃ for 4 hours to obtain the powder. It was reported that it could be used as a candidate material for LTCC technology. In the document "Structure and microwave dielectric properties of glass free low temperature co-firable SrMV2O7 (M=Mg, Zn) ceramics", the traditional solid phase method was also used to prepare ceramic powder. First, the raw material was wet mixed in distilled water for 1 hour, then dried at 80℃, and finally calcined at 650 and 600℃ for 4 hours to obtain the powder. It was reported that it could be a candidate material for ULTCC technology.
[0003] At present, most methods for preparing microwave dielectric ceramic powders adopt high-temperature solid-phase methods, which have the problems of high preparation temperature, long preparation time and large particle size, resulting in high sintering temperature and poor sintering quality of ceramics. The present invention adopts a new approach to prepare high-purity SrZnV2O7 ceramic powders. Compared with the traditional method, it has the advantages of lower preparation temperature and shorter calcination time, and improves the agglomeration phenomenon of the sample. The obtained powder particles are dispersed and uniform in particle size, which is conducive to improving the sintering quality in the later stage. Summary of the invention
[0004] The purpose of the present invention is to provide a new technical route for preparing SrZnV2O7 microwave dielectric ceramic powder, which can effectively solve the problems of high preparation temperature, long preparation time, easy generation of impurities and particle agglomeration in the prior art.
[0005] The technical solution of the present invention is:
[0006] A method for preparing SrZnV2O7 microwave dielectric ceramic powder in a short time comprises the following steps:
[0007] (1) Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed as raw materials in a molar ratio of 1:1:2:(6-8);
[0008] (2) adding the NH4VO3 weighed in step (1) into water and continuously stirring in a water bath at 80°C until completely dissolved, with a concentration of 0.16 to 0.187 mol / L;
[0009] (3) Add the Sr(NO3)2, Zn(NO3)2·6H2O and C2H5NO2 weighed in step (1) into water and stir continuously at room temperature until they are completely dissolved. 2+ The concentration of Zn is 0.12~0.14mol / L, 2+ The concentration of is 0.12~0.14mol / L, and the concentration of C2H5NO2 is 0.72~1.12mol / L;
[0010] (4) mixing the solutions obtained in step (2) and step (3), and stirring in a water bath at 70° C. for 2 to 3 hours to obtain a sol;
[0011] (5) completely drying the sol obtained in step (4) at 120° C. to obtain a xerogel;
[0012] (6) Grinding the dry gel obtained in step (5) and calcining it at 500-700° C. for 5 min-2 h to obtain SrZnV2O7 material.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The present invention adopts a new preparation method, and can prepare SrZnV2O7 material by calcining at a low temperature of 600°C for 5 minutes. Compared with the high-temperature solid-phase method, the preparation temperature is lowered, the preparation time is shortened, and the production energy consumption is effectively reduced;
[0015] (2) The prepared SrZnV2O7 material has uniform particles, small particle size and improved particle agglomeration, which is beneficial to the subsequent sintering. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD patterns of the SrZnV2O7 ceramic powders prepared in Examples 1 to 4 are shown in Figure 1, Figure 2, Figure 3, and Figure 4.
[0017] Figure 2 The XRD patterns of SrZnV2O7 ceramic powders prepared in Examples 5 to 7 are shown in Figure 5, Figure 6, and Figure 7.
[0018] Figure 3 These are SEM images of the SrZnV2O7 ceramic powder prepared in Example 1, where (a) is a 2 μm scale and (b) is a 500 nm scale. DETAILED DESCRIPTION
[0019] In order to better understand the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0020] Example 1
[0021] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6. 2+ The concentration of Zn is 0.12mol / L. 2+The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.72mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 600°C and a calcination time of 2h. After the reaction is completed, it is naturally cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0022] Example 2
[0023] The difference between this embodiment and embodiment 1 is that the calcination time is 1 hour. The specific preparation method is as follows:
[0024] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6. 2+ The concentration of Zn is 0.12mol / L. 2+ The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.72mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 600°C and a calcination time of 1h. After the reaction is completed, it is cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0025] Example 3
[0026] The difference between this embodiment and embodiments 1 and 2 is that the calcination time is 30 minutes. The specific preparation method is as follows:
[0027] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6. 2+ The concentration of Zn is 0.12mol / L. 2+ The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.72mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 600°C and a calcination time of 30min. After the reaction is completed, it is cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0028] Example 4
[0029] The difference between this embodiment and embodiments 1 to 3 is that the calcination time is 5 minutes. The specific preparation method is as follows:
[0030] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6. 2+ The concentration of Zn is 0.12mol / L. 2+ The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.72mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 600°C and a calcination time of 5min. After the reaction is completed, it is cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0031] Example 5
[0032] The main difference between this embodiment and embodiments 1 to 4 is that the calcination temperature is 700° C. The specific preparation method is as follows:
[0033] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6. 2+ The concentration of Zn is 0.12mol / L. 2+ The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.72mol / L. Then, solution A is mixed with solution B, stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and dried at 120°C for 6h to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 700°C and a calcination time of 2h. After the reaction is completed, it is naturally cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0034] Example 6
[0035] The main difference between this embodiment and embodiments 1 to 5 is that the calcination temperature is 500° C. The specific preparation method is as follows:
[0036] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:6. 2+ The concentration of Zn is 0.12mol / L. 2+The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.72mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 500°C and a calcination time of 2h. After the reaction is completed, it is naturally cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0037] Example 7
[0038] The main difference between this embodiment and embodiments 1 to 6 is that the molar ratio of the raw materials is Sr(NO3)2:Zn(NO3)2·6H2O:NH4VO3:C2H5NO2=1:1:2:8. The specific preparation method is as follows:
[0039] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio of Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:8. First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.16 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr 2+ The concentration of Zn is 0.12mol / L. 2+ The concentration of is 0.12mol / L, and the concentration of C2H5NO2 is 0.96mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 2h to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 600°C and a calcination time of 1h. After the reaction is completed, it is naturally cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0040] Example 8
[0041] The difference between this embodiment and embodiments 1 to 7 is that the concentration of each reaction raw material is increased, and the stirring time after the two solutions are mixed is prolonged. The specific preparation method is as follows:
[0042] Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and glycine (C2H5NO2) were weighed according to the molar ratio (Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:8). First, NH4VO3 was added to water and stirred continuously in a water bath at 80°C until it was completely dissolved to obtain solution A with a concentration of 0.187 mol / L. Sr(NO3)2, Zn(NO3)2·6H2O and glycine (C2H5NO2) were added to water and stirred continuously at room temperature until it was completely dissolved to obtain solution B, in which Sr(NO3)2: Zn(NO3)2·6H2O: NH4VO3: C2H5NO2 = 1:1:2:8. 2+ The concentration of Zn is 0.14 mol / L. 2+ The concentration of is 0.14 mol / L, and the concentration of C2H5NO2 is 1.12 mol / L. Then, solution A is mixed with solution B, and stirred in a water bath at 70°C for 3 hours to obtain a sol, and the obtained sol is transferred to an oven and completely dried at 120°C to obtain a dry gel. Finally, the obtained dry gel is ground and transferred to a muffle furnace, and calcined in an air atmosphere at a calcination temperature of 600°C and a calcination time of 2 hours. After the reaction is completed, it is naturally cooled to obtain SrZnV2O7 microwave dielectric ceramic powder.
[0043] Figure 1 and Figure 2 This is the XRD spectrum of the SrZnV2O7 microwave dielectric ceramic powder prepared in Examples 1 to 7. It can be seen from the XRD spectrum that the diffraction peak is high and no impurity peak appears, indicating that a SrZnV2O7 material with high crystallinity is generated.
[0044] The above embodiments describe the basic principles and main features of the present invention, but the above are only specific embodiments of the present invention, and the technical features of the present invention are not limited thereto. All implementation schemes that meet the requirements of the present invention belong to the scope of the present invention.
Claims
1. A method for preparing SrZnV2O7 microwave dielectric ceramic powder in a short time, characterized in that: Here are the steps: (1) Sr(NO3)2, Zn(NO3)2·6H2O, NH4VO3 and C2H5NO2 were weighed as raw materials in a molar ratio of 1:1:2:(6-8); (2) adding the NH4VO3 weighed in step (1) into water and continuously stirring in a water bath at 80°C until completely dissolved, with a concentration of 0.16-0.187 mol / L; (3) Add the Sr(NO3)2, Zn(NO3)2·6H2O and C2H5NO2 weighed in step (1) into water and stir continuously at room temperature until they are completely dissolved. 2+ The concentration of Zn is 0.12~0.14 mol / L. 2+ The concentration of is 0.12~0.14 mol / L, and the concentration of C2H5NO2 is 0.72~1.12 mol / L; (4) mixing the solutions obtained in step (2) and step (3), and stirring in a 70° C. water bath for 2 to 3 h to obtain a sol; (5) completely drying the sol obtained in step (4) at 120° C. to obtain a xerogel; (6) Grinding the dry gel obtained in step (5) and calcining it at 500-700° C. for 5 min-30 min to obtain SrZnV2O7 material.
Citation Information
Patent Citations
Method for preparing BaCaV2O7 microwave dielectric ceramic material at low temperature
CN112624762A